The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13073-016-0320-1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive promoter level expression quantitative trait loci analysis of the human frontal lobe

Abstract: BackgroundExpression quantitative trait loci (eQTL) analysis is a powerful method to detect correlations between gene expression and genomic variants and is widely used to interpret the biological mechanism underlying identified genome wide association studies (GWAS) risk loci. Numerous eQTL studies have been performed on different cell types and tissues of which the majority has been based on microarray technology.MethodsWe present here an eQTL analysis based on cap analysis gene expression sequencing (CAGEse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 91 publications
(126 reference statements)
2
21
0
Order By: Relevance
“…17 Samples with complete data for the relevant SNPs included 77 males and 33 females with mean age = 51 years (range = 2–95), mean RNA integrity number (RIN) = 7.6 (range = 5.4–9.1), and mean postmortem interval = 11 hours (range = 2–28). Findings were followed up in available data from an ongoing RNA sequencing (RNAseq) study by the North American Brain Expression Consortium (dbGAP phs001300.v1.p1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…17 Samples with complete data for the relevant SNPs included 77 males and 33 females with mean age = 51 years (range = 2–95), mean RNA integrity number (RIN) = 7.6 (range = 5.4–9.1), and mean postmortem interval = 11 hours (range = 2–28). Findings were followed up in available data from an ongoing RNA sequencing (RNAseq) study by the North American Brain Expression Consortium (dbGAP phs001300.v1.p1).…”
Section: Methodsmentioning
confidence: 99%
“…We reanalyzed postmortem frontal cortex cap analysis gene expression sequencing (CAGEseq) data and imputed genotypes from the SNCA locus from 117 neurologically normal individuals, where materials and methods have been described in detail in a previous publication. 17 Samples with complete data for the relevant SNPs included 77 males and 33 females with mean Samples overlapping with CAGEseq were removed, leaving a total of 150 nonneurological frontal cortex samples with nonmissing genotype data for 55 males and 86 females with mean age = 59 years (range =15-97), mean RIN = 7.7 (range = 6.0-9.5), and mean postmortem interval = 10.0 hours (range = 1.2-36.0). The use of human brain samples from both of these datasets was approved by the NIH Office for Human Subjects Research.…”
Section: Expression Quantitative Trait Locus Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…We also applied MOSTWAS to transcriptomic data on samples of prefrontal cortex, a tissue that has been used previously in studying neuropsychiatric traits and disorders with TWAS [58,59]. There has been ample evidence in brain tissue, especially the prefrontal cortex, that non-coding variants may regulate distal genes [58,60,61]; in fact, an eQTL analysis by Sng et al found that approximately 20-40% of eQTLs in the frontal cortex can be considered trans-acting [62]. Thus, the prefrontal cortex in the context of neuropsychiatric disorders provides a prime example to assess MOSTWAS.…”
Section: Real Data Application In Brain Tissuementioning
confidence: 99%